Sequence and structure of the yeast galactose transporter. - Szkutnicka, K (1989)
The previously cloned GAL2 gene of the Saccharomyces cerevisiae galactose transporter has been sequenced. The nucleotide sequence predicts a protein with 574 amino acids (Mr, 63,789). Hydropathy plots suggest that there are 12 membrane-spanning segments. The galactose transporter shows both sequence and structural homology with a superfamily of sugar transporters which includes the human HepG2-erythrocyte and fetal muscle glucose transporters, the rat brain and liver glucose transporters, the Escherichia coli xylose and arabinose permeases, and the S. cerevisiae glucose, maltose, and galactose transporters. Sequence and structural motifs at the N-terminal and C-terminal regions of the proteins support the view that the genes of this superfamily arose by duplication of a common ancestral gene. In addition to the sequence homology and the presence of the 12 membrane-spanning segments, the members of the superfamily show characteristic lengths and distributions of the charged, hydrophilic connecting loops. There is indirect evidence that the transporter is an N-glycoprotein. However, its only N-glycosylation site occurs in a charged, hydrophilic segment. This could mean that this segment is part of a hydrophilic channel in the membrane. The transporter has a substrate site for the cyclic AMP-dependent protein kinase which may be a target of catabolite inactivation. The transporter lacks a strong sequence enriched for proline (P), glutamate (E), aspartate, serine (S), and threonine (T) and flanked by basic amino acids (PEST sequence) even though it has a short half-life. Mechanisms for converting the poor PEST to a possible PEST sequence are considered. Like the other members of the superfamily, the galactose transporter lacks a signal sequence.